2007
DOI: 10.1007/s00449-007-0129-9
|View full text |Cite
|
Sign up to set email alerts
|

Lipase-catalyzed esterification of conjugated linoleic acid with l-carnitine in solvent-free system and acetonitrile

Abstract: Lipase-catalyzed esterification of conjugated linoleic acid (CLA) with L-carnitine in solvent-free system and acetonitrile was studied. Three lipases (Novzym 435, Amamo AY30 and Amano AYS) have been assayed as suitable biocatalysts in the reaction. It was found that Amano AY30 was the most effective biocatalyst in both solvent-free system and acetonitrile. The conversion rate varied from 8.05 to 60.9% in terms of reaction conditions such as the amount of lipase, the presence of water, the amount of molecular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Acylation reactions can be performed in the presence of inorganic catalysts, but several studies reported that chemical esterification is not regioselective and results in unwanted functionalization of phenolic hydroxyl groups, which are responsible for antioxidant activity. On the other hand, lipases are widely recognized as suitable catalysts for obtaining various products due to their chemo-, regio-, and enantioselectivities, as well as low prices and availability. In accordance with this, enzymatic acylation of flavonoids catalyzed by lipases (triacylglycerol acylhydrolase, EC 3.1.1.3) is an attractive alternative, since it is more regioselective than chemical acylation and may improve not only their solubility in various media, but also their stability and their antioxidant activity. , Also, using lipase as a catalyst allows the use of much milder reaction conditions and gives higher yields, better product quality, and lower downstream processing costs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acylation reactions can be performed in the presence of inorganic catalysts, but several studies reported that chemical esterification is not regioselective and results in unwanted functionalization of phenolic hydroxyl groups, which are responsible for antioxidant activity. On the other hand, lipases are widely recognized as suitable catalysts for obtaining various products due to their chemo-, regio-, and enantioselectivities, as well as low prices and availability. In accordance with this, enzymatic acylation of flavonoids catalyzed by lipases (triacylglycerol acylhydrolase, EC 3.1.1.3) is an attractive alternative, since it is more regioselective than chemical acylation and may improve not only their solubility in various media, but also their stability and their antioxidant activity. , Also, using lipase as a catalyst allows the use of much milder reaction conditions and gives higher yields, better product quality, and lower downstream processing costs.…”
Section: Introductionmentioning
confidence: 99%
“…6−10 In accordance with this, enzymatic acylation of flavonoids catalyzed by lipases (triacylglycerol acylhydrolase, EC 3.1.1.3) is an attractive alternative, since it is more regioselective than chemical acylation and may improve not only their solubility in various media, but also their stability and their antioxidant activity. 5,11 Also, using lipase as a catalyst allows the use of much milder reaction conditions and gives higher yields, better product quality, and lower downstream processing costs. So far, to the authors' best knowledge, publications referring to phloridzil ester synthesis have been very rare.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [111] reported that the addition of molecular sieves increased the rate and conversion yield; this is due to the efect of the molecular sieves to sequester the water layer from the enzyme molecule which is essential for the water-enzyme interaction. Mellou et al [112] found that the conversion yield of rutin during esteriication reaction with oleic acid catalyzed by immobilized C. antarctica lipase B in diferent solvents was varied from 37 to 71% under the use of molecular sieves (100 mg/ ml).…”
Section: Molecular Sievementioning
confidence: 99%